A Compilation of the Acts of the Legislature Incorporating the City of Macon, Georgia 48 (1858) - (:unkn) unknown (My University, 1858)
§ 5:§It shall not be lawful for any person to fire a gun, pistol, or any other fire arms, within three hundred yards of any house, except in cases of military parade; nor shall any person burn rockets, crackers, or any kind of fireworks within the limits of the city. Any person so offending shall be fined in a sum not exceeding twenty dollars.
Keywords: DISCHARGE